Forming Student Confidence through Seven-Minute Lecture Activities at Islamic Elementary School - Hasanah, Afdinda Tawaffanal; Rozi, Fakrur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study is entitled "Establishment of Confidence through a Seven Minute Lecture for Students of Baitul Huda Semarang Madrasah (MI)" with issues that focus on: (1) How to Build Self-Confidence through a Seven Minute Lecture for Students of Madrasah Bidayuh (MI) Baitul Huda Semarang, (2) What are the contributions of the Seven Minute Lecture in Building the Confidence of Students MI Baitul Huda Semarang. A qualitative approach is used in this study, with primary and secondary data sources, using data collection techniques in the form of observation, interviews, and documentation and documentation and data analysis in the form of data reduction, data presentation, and data analysis drawing conclusions. The results of the study suggest the following: forming the self-confidence of MI Baitul Huda Semarang students through a cult whose implementation when after dhikr the Duur prayer is in congregation at the mosque, there are obstacles regarding the lack of enthusiasm of students in listening to their friends who are in charge of delivering a Seven Minute Lecture, and if students forget to prepare the material that will be delivered for the Seven Minute Lecture. The contribution of the Seven Minute Lecture activity in building the confidence of fifth-grade students of MI Baitul Huda Semarang is that students are more self-confident, such as not hesitating or being embarrassed or afraid when expressing opinions in class, such as when discussing and answering teacher questions. Then little by little, he was no longer afraid when delivering the Seven Minute Lecture material in front of his friends. In addition, it can add insight into religious issues. Then introduce students to the field of da'wah.